'Rothia nasisuis' sp. nov., 'Dermabacter porcinasus' sp. nov., 'Propionibacterium westphaliense' sp. nov. and 'Tessaracoccus nasisuum' sp. nov., isolated from porcine nasal swabs in the Münster region, Germany. (November 2018) - Schlattmann, A.; von Lützau, K.; Kaspar, U.; Becker, K.
Abstract: We report the core features of 'Rothia nasisuis' strain 1a5R-CH16 sp. nov., 'Dermabacter porcinasus' strain 2a1I-BL09 sp. nov., 'Propionibacterium westphaliense' strain 1a7I-CH12an sp. nov. and 'Tessaracoccus nasisuum' strain 1a6R-CH11an sp. nov. In 2016, these isolates were cultured from porcine nasal swabs taken from healthy pigs from farms in the region around Münster, Germany.